Transtorno de ansiedade social e insatisfação com a imagem corporal em estudantes de medicina: prevalência e fatores associados - Regis, Jacqueline Maria de Oliveira [UNESP] (2015)
Introduction: Previous studies described high prevalence rates of Social Anxiety Disorder (SAD) (or Social Phobia) and of body image dissatisfaction (BID) in college students. Manifestations of these clinical problems may cause much suffering and negatively interfere in the students' life, both in their interpersonal relationships and academic performance. Objectives: To estimate the prevalence and severity of SAD and BID manifestations in medical students of a public university in São Paulo state, Brazil, as well as to investigate the characteristics associated with these outcomes. Method: A cross-sectional study with 479 students from the first to the sixth year of the medical course at Botucatu Medical School - UNESP (response rate: 88.1%), using the following assessment instruments: a questionnaire to obtain data on demographics and social and academic life,, the Social Phobia Inventory (SPIN), the Body Shape Questionnaire (BSQ), and the Beck Depression Inventory (BDI). A descriptive analysis was conducted, followed by a bivariate analysis between the outcomes (probable SAD and BID) and all explanatory variables, using the chi - square test for categorical variables and the Mann-Whitney test for quantitative variables. The effect sizes of the associations were described as odds ratios (OR) with 95% confidence intervals (CI) for categorical variables, and Cohen's D for quantitative variables. Then, three logistic regression models (for probable SAD, BID and both outcomes combined) were built, including, in each of them, the explanatory variables that were significant (p<0.05) in the bivariate analysis to control for confounders and obtain adjusted ORs. Results: The median age of the students (58.7% female, 99.0% single) was 22.5 years (SD±2.6). The prevalence of probable SAD (SPIN ≥ 19) was 36.3% (95%CI 32.0-40.6), and some BID (BSQ > 81) was found in 34.7% (95%CI 30.4-38.9) of the students. Relevant depressive symptoms ...